2013
DOI: 10.1002/art.38110
|View full text |Cite
|
Sign up to set email alerts
|

A Genome‐Wide Association Study Reveals ARL15, a Novel Non‐HLA Susceptibility Gene for Rheumatoid Arthritis in North Indians

Abstract: Objective. Genome-wide association studies (GWAS) and their subsequent meta-analyses have changed the landscape of genetics in rheumatoid arthritis (RA) by uncovering several novel genes. Such studies are heavily weighted by samples from Caucasian populations, but they explain only a small proportion of total heritability. Our previous studies in genetically distinct North Indian RA cohorts have demonstrated apparent allelic/genetic heterogeneity between North Indian and Western populations, warranting GWAS in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
33
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 44 publications
(36 citation statements)
references
References 40 publications
2
33
0
1
Order By: Relevance
“…This was supported by a GWAS on rheumatoid arthritis that we recently conducted in an NI cohort in which we identified a novel non-HLA gene, ARL15 27. These findings reiterate the importance of conducting GWASs in different ethnic groups.…”
Section: Discussionsupporting
confidence: 70%
“…This was supported by a GWAS on rheumatoid arthritis that we recently conducted in an NI cohort in which we identified a novel non-HLA gene, ARL15 27. These findings reiterate the importance of conducting GWASs in different ethnic groups.…”
Section: Discussionsupporting
confidence: 70%
“…This gene is also in a common network with the RA-associated gene ARL15 (Supplementary Fig. 3; Supplemental digital content 4, http://links.lww.com/FPC/A697), which correlates with serum adiponectin level and tissue inflammation [20]. Underexpression of WWOX genes is known for cancer pathogenesis [46] that acts through several p53 family proteins and participates in growth suppression, differentiation, and transcription modulation [47].…”
Section: Discussionmentioning
confidence: 98%
“…SNPs were ranked on the basis of their weight, where higher weight indicates more relevant SNPs for the phenotype. The SVM approach has been used successfully in many studies to identify susceptibility variants [20,[25][26][27] and the detailed methodology has been described elsewhere [20]. It is well known that when the number of SNPs are larger than the number of individuals, the performance of the SVM reduces.…”
Section: Support Vector Machine Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…The shared epitope (SE) theory provided insight into the association between the susceptibility of RA and some specific HLA class II genotypes such as DRB1 and DRQ1 [16][17][18][19]. However, recent investigations have indicated that more non-MHC genes may be associated with RA susceptibility, such as PTPN22, PADI4, TRAF1-C5, STAT4, and ARL15 [20][21][22][23][24][25][26][27]. In our previous work, we identified Tespa1 [7], a gene that interacted with the linker for activation of T cells (LAT) signalosome formed during TCR signaling, thus playing a key role in the regulation of T cell development.…”
Section: Discussionmentioning
confidence: 97%